Die Menigte rondom Jesus - Botha, P. J. J. (Verbum et ecclesia, 1998)
The crowds around Jesus This article is an exercise in historical imagination. By employing an interdisciplinary approach some facets of the appearance and daily experiences of first century Galilean peasants are discussed. The question, how we should picture Jesus’ crowds, thereby becomes a powerful way of opening a window onto the world of the historical Jesus.